Indigenous Watershed Management for Sustainable Framework at Besao, Mountain Province - Omaney, Mileatte; Wacangan, Vicente; Bao-idang, Conrado; Ngiwas, Sano (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined sustainable indigenous watershed management in Besao, Mountain Province, by integrating traditional forest management practices, customary guiding principles, land uses, forest cover, slope conditions, and government policies and programs. Its conceptual framework considered traditional forest management, forest cover, and slope classification alongside land uses, indigenous principles, and government interventions as bases for developing a sustainable watershed management framework. The study employed a qualitative research design involving 140 Applai indigenous household members aged 50 years and above, particularly elders and leaders engaged in traditional watershed management. Data were obtained through focus group discussions, community mapping, field visits, on-site observations, photo documentation, secondary sources, and GIS-based analysis using land cover maps, slope data, and QGIS software. The findings revealed that all 14 barangays implemented forest protection measures, including regular foot patrols, community warning systems, voluntary fire suppression, restricted tree harvesting, and spring protection. Forest maintenance involved assisted natural regeneration, wildling management, cultural practices, and fire-line establishment, while forest development included biodiversity conservation and community-based ecotourism. Community mapping identified 7,545.45 hectares of protection forest, 4,153.30 hectares of production forest or Batangan, and 6,491.89 hectares of multiple-use areas. The results showed that sustainable watershed management was strengthened by customary laws, collective responsibility, cultural beliefs, regulated resource use, and community participation. However, steep terrain, landslide susceptibility, forest fires, timber poaching, encroachment, water scarcity, and inappropriate land use remained important concerns. The study concluded that indigenous forest management effectively supports watershed protection and the responsible use of forest resources. It recommended strengthening partnerships between local government units and communities, formally integrating indigenous knowledge into local policies, rehabilitating degraded forestlands, stabilizing slopes, and clearly demarcating protection, production, and multiple-use areas. The study supports SDG 6, SDG 11, SDG 15, and SDG 17 through water protection, community-based governance, sustainable land and forest management, and institutional partnerships. Its sustainability impact lies in strengthening ecological protection, cultural continuity, community livelihoods, spatial planning, and locally grounded environmental governance.
Keywords: Batangan; Community Participation; Forest Management; Geographic Information System; Indigenous Knowledge; Land Use Planning; Slope Analysis; Sustainable Watershed Management; Watershed Governance